PENINGKATAN KEMAMPUAN GURU DALAM PENGEMBANGAN MODUL AJAR BERBASIS KETERAMPILAN BERPIKIR KRITIS UNTUK GURU IPA DI SMP NEGERI 1 BAKTIRAJA - Imelda Simamora, Ince; Nancy Susianna; Nerru Pranuta Murnaka; Alvin Stanza Kiswandhi (Jurnal Tunas Pendidikan, 2025)
This study aims to improve the ability of science teachers to develop teaching modules based on critical thinking skills at SMP Negeri 1 Baktiraja. It compares the effectiveness of online and offline teacher training methods. The research employed an experimental design involving two groups of teachers who received training in different formats. The first group participated in online training through a digital learning platform, while the second group attended offline training conducted face-to-face. The population of this study comprised all public junior high schools under the UPTD of Humbang Hasundutan Regency. The samples selected were UPT SMP Negeri 019 Sibuntuon and UPT SMP Negeri 001 Pasar Doloksanggul, chosen through purposive sampling. The study was conducted over a period of six days. The research instrument used was a test, with data collected through pre-tests and post-tests to measure the improvement in teachers' abilities to develop critical thinking-based teaching modules. Additionally, observations and interviews were conducted to explore participants’ experiences during the training sessions. The results showed that both training methods significantly improved teacher competence. However, there were notable differences in certain aspects. Offline training was found to be more effective in enhancing teachers' abilities to develop critical thinking-based teaching modules. This was attributed to direct interaction, in-depth discussions, and hands-on practice. In contrast, while online training also led to improvements, its effectiveness was lower due to limited direct interaction, fewer in-depth discussions, and challenges in providing structured practice. Nevertheless, online training offered flexibility and broader accessibility, enabling more teachers to participate regardless of geographic location.